Breaking the silence about obstetric violence: Body mapping women's narratives of respect, disrespect and abuse during childbirth in Bihar, India - Kaveri Mayra; Jane Sandall; Zoë Matthews; Sabu S. Padmadas (BMC, 2022)
Abstract Background Evidence on obstetric violence is reported globally. In India, research shows that almost every woman goes through some level of disrespect and abuse during childbirth, more so in states such as Bihar where over 70% of women give birth in hospitals. Objective 1) To understand how women experience and attach meaning to respect, disrespect and abuse during childbirth; and 2) document women's expectations of respectful care. Methods 'Body mapping', an arts-based participatory method, was applied. The analysis is based on in-depth interviews with eight women who participated in the body mapping exercise at their homes in urban slums and rural villages. Analysis was guided by feminist relational discourse analysis. Findings Women reported their experiences of birthing at home, public facilities, and private hospitals in simple terms of what they felt 'good' and 'bad'. Good experiences included being spoken to nicely, respecting privacy, companion of choice, a bed to rest, timely care, lesser interventions, obtaining consent for vaginal examination and cesarean section, and better communication. Bad experiences included unconsented interventions including multiple vaginal examinations by different care providers, unanesthetized episiotomy, repairs and uterine exploration, verbal, physical, sexual abuse, extortion, detention and lack of privacy. Discussion The body maps capturing birth experiences, created through a participatory method, accurately portray women's respectful and disrespectful births and are useful to understand women's experience of a sensitive issue in a patriarchal culture. An in-depth understanding of women's choices, experiences and expectations can inform changes practices in and policies and help to develop a culture of sharing birth experiences.